2020
DOI: 10.1021/acs.jpcc.0c01933
|View full text |Cite
|
Sign up to set email alerts
|

CuInS2-Doped ZnS Quantum Dots Obtained via Non-Injection Cation Exchange Show Reduced but Heterogeneous Blinking and Provide Insights into Their Structure–Optical Property Relationships

Abstract: Cadmium-free CuInS2-doped ZnS quantum dots (QDs) are synthesized through a two-step non-injection synthetic method. The resulting QDs are small (∼8 nm or less) and relatively isotropic with photoluminescence quantum yields (PL QY) up to almost 70% and emission peaks in the 560–600 nm window, depending on the amount of the Zn precursor added. The results indicate that small CuInS2 clusters within a zinc blende ZnS lattice are the radiative recombination centers in the nanoparticle. Interestingly, higher ensembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
0
13
0
1
Order By: Relevance
“…Single-particle spectroscopy has been proven essential to understand various aspects of the photophysics of QDs, as it yields data that are not obscured by ensemble-averaging. Unfortunately, CIS QDs are notoriously unstable under the harsh excitation conditions used in single-QD experiments. , Consequently, single-particle studies on CIS-based QDs are scarce ,,, and achieve limited data quality compared to studies on other types of QDs. Most strikingly, Whitham et al reported broad single-QD PL line widths (minimum fwhm, 190 meV) from individual core/shell CIS/CdS QDs, whereas Zang et al found narrow PL line widths (minimum fwhm, 60 meV) from individual core/shell CIS/ZnS QDs .…”
mentioning
confidence: 99%
“…Single-particle spectroscopy has been proven essential to understand various aspects of the photophysics of QDs, as it yields data that are not obscured by ensemble-averaging. Unfortunately, CIS QDs are notoriously unstable under the harsh excitation conditions used in single-QD experiments. , Consequently, single-particle studies on CIS-based QDs are scarce ,,, and achieve limited data quality compared to studies on other types of QDs. Most strikingly, Whitham et al reported broad single-QD PL line widths (minimum fwhm, 190 meV) from individual core/shell CIS/CdS QDs, whereas Zang et al found narrow PL line widths (minimum fwhm, 60 meV) from individual core/shell CIS/ZnS QDs .…”
mentioning
confidence: 99%
“…The cation exchange method can be further applied to other bimetallic or trimetallic chalcogenides like phase segregated Cu–Au sulfides, 40 Cu–Ni selenides, 56 Cu–Co sulfides nanoboxes, 57 and CuInS 2 -doped ZnS, 58 and could potentially be used for multifunctional photo/electrocatalysis. With modifications of ligands or additives during the cation exchange method, may realize the control of even vs. uneven distribution of two elements with the same overall concentration that can be employed as a great test field for mechanism investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The cation exchange method can be further applied to other bimetallic or trimetallic chalcogenides like phase segregated Cu-Au sulfides, 39 Cu-Ni selenides, 53 Cu-Co sulfides nanoboxes, 54 and CuInS 2 -doped ZnS, 55 and could potentially be used for multifunctional photo/electrocatalysis. With modifications of ligands or additives during the cation exchange method, may realize the control of even vs. uneven distribution of two elements with the same overall concentration that can be employed as a great test field for mechanism investigation.…”
Section: Discussionmentioning
confidence: 99%